Return of State Losses In The Investigation Process That Can Eliminate Criminal Perpetrators of Corruption - Andi Mirzan Doda; Fence M. Wantu; Dian Ekawaty Ismail (Estudiante Law Journal, 2023)
The purpose of writing to be achieved in this paper is to know and analyze the return of state losses in the investigation process that can eliminate criminal perpetrators of corruption.  This research is a normative legal research using  the statutory approach "statute approach", the case approach "case approach", and the  conceptual approach "conceptual approach".  This study used analytical descriptive analysis techniques. The results of this study show that the return of state financial losses in the investigation stage of corruption can stop the process of handling criminal acts through police discretion. One of the elements of corruption is the element of state loss, meaning that when it has been returned, it means that the element has been lost, meaning there is no loss as a logical consequence of the Constitutional Court decision No. 25/PUU-XIV/2016. But with the condition that it must be before the investigation stage through police discretion and if it is based on  the Lex Posterior Derogate Lege Priori, meaning that the new law overrides the old  law, meaning that the new regulation ignores or overrides the old regulation in the same respect